Reconceptualizing halal tourism for the digital influence and sustainable age - Roslan, Farah Syuhada; Misaridin, Nur Aulia Fahada (Journal of Islamic, Social, Economics and Development, 2025)
Halal tourism has typically been conceptualized in a compliance-based paradigm, with a focus on tangible amenities. However, this approach fails to represent the nuances of the modern Muslim traveler, who is heavily impacted by digital media and has a growing commitment to sustainable and ethical consuming practices. Today's Muslim tourist is not only technologically connected and influenced through social media, but they are also more concerned with integrated ethical consumerism, which includes environmental and social sustainability. To address this gap, a theory synthesis strategy will be used to reconfigure and expand the domain theory of Halal tourism. This paper concludes by proposing a novel framework that redefines Halal tourism as a value-driven experience, co-created through digital trust and a commitment to multi-stakeholder well-being. This reconceptualization provides a new theoretical lens for tourism and marketing scholars and offers practical strategies for destinations and influencers to effectively engage the growing market of conscious Muslim travelers.